2016
DOI: 10.1186/s12885-016-2975-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for palliative treatment of locally advanced or metastatic gastric cancer and adenocarcinoma of the gastroesophageal junction: a choice-based conjoint analysis study from Germany

Abstract: BackgroundDecisions on palliative chemotherapy (CT) for locally advanced or metastatic gastric cancer (mGC) require trade-offs between potential benefits and risks for patients. Healthcare providers and payers agree that patient-preferences should be considered. We conducted a choice-based conjoint (CBC) analysis study in pre-treated patients from Germany with mGC or locally advanced or metastatic adenocarcinoma of the gastroesophageal junction (mGEJ-Ca), to evaluate their preferences when hypothetically selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…The core of conjoint analysis relies on the untangling of the complex tradeoffs patients unconsciously make when selecting one drug product over another, allowing for the objective qualification of patient preferences. Based on the reliability of this unbiased analysis methodology, its use to measure patient preferences has increased in health care research where health authorities such as the U.S. Food and Drug Administration (Center for Devices and Radiological Health) also value its utility (33)(34)(35)(36). Other strengths of the survey are the clinical applicability and relevance of the data generated, given the baseline clinical characteristics of the selected respondent population.…”
Section: Discussionmentioning
confidence: 99%
“…The core of conjoint analysis relies on the untangling of the complex tradeoffs patients unconsciously make when selecting one drug product over another, allowing for the objective qualification of patient preferences. Based on the reliability of this unbiased analysis methodology, its use to measure patient preferences has increased in health care research where health authorities such as the U.S. Food and Drug Administration (Center for Devices and Radiological Health) also value its utility (33)(34)(35)(36). Other strengths of the survey are the clinical applicability and relevance of the data generated, given the baseline clinical characteristics of the selected respondent population.…”
Section: Discussionmentioning
confidence: 99%
“…Using conjoint analysis techniques may help in identification of trends in general patient preferences over time and detection of relevant shifts in culture. Interestingly, among other recent studies an excellent study by Ballinger et al found patients to tend to favor toxicity concerns over treatment benefit ( 11 , 13 ), while older studies often found survival benefit to be of supreme importance ( 16 , 28 30 ). Clinical trials on population level generally focus on survival benefit as the primary endpoint and most critical aspect of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the technique of conjoint analysis is widely used in the medical and non-medical field for assessment of preferences and has been demonstrated to offer a valuable tool to elicit patient preferences or utilities for specific treatments ( 11 14 ). In regard to medical treatment, conjoint analysis has proven to be useful for preference elicitation mainly in cancer therapy ( 11 , 13 , 15 , 16 ). By having participants evaluate alternatives and letting them choose between different combinations of attributes, the relative importance of each attribute can be deducted ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is commonly used both in scientific research and business analysis. Looking at the latest researches with conjoint usage, it can be noticed that the range of usage is very broad: from business and consumer preferences research [Meyerding 2016], across medicine and patient preferences [Hofheinz et al 2016], housing market [Rofè, Pashtan, Hornik 2017] and even hotels and restaurants [Lee 2016].…”
Section: How To Use It?mentioning
confidence: 99%